Correction of the type locality of Neomorphus geoffroyi (Temminck, 1820), with lectotype designation - Raposo, Marcos A.; Simon, José Eduardo; Teixeira, Dante Martins (Zootaxa, 2009)
Neomorphus geoffroyi was described without reference to a locality (Temminck 1820, the plate only and Temminck 1823, the text). Pará, Brazil, is currently considered the type locality of the species (e.g., Payne 1997, 2005), following Peters (1940). This designation contrasts with the earlier conclusion of Hellmayr (1905), who considered Bahia the probable provenance of the specimens described by Temminck (1820). Peters (1940) presented no detailed justification for changing the type locality and only commented that “the original description and plate do not agree with Bahia specimens”, providing no indication as to which characters in the original description were inconsistent with Bahia specimens (and consistent with the specimens from Pará).